Dental management of hypohidrotic ectodermal dysplasia: A report of two cases - Meenu Mittal; Dhirendra Srivastava; Ashok Kumar; Poonam Sharma (Wolters Kluwer Medknow Publications, 2015)
Ectodermal dysplasia (ED) represents a group of inherited conditions characterized by anomalies in two or more structures of ectodermal origin, which can be presented as problems related to hair, nail, teeth, sweat glands, and sebaceous glands. Based on clinical findings, there are two major types of this disorder: (1) Hypohidrotic/anhidrotic and (2) hidrotic ED. The anhidrotic/hypohidrotic ED (HED) is the more severe form and is associated with more dental defects. This article presents with prosthetic rehabilitation including removable partial and complete denture and implant supported overdenture of two male children of a family presenting with HED.